The adaptation of four orthorexia nervosa scales into Turkish population - Bilekli Bilger, İlgün; Dağ, İhsan (JOHN WILEY & SONS LTD, 2023)
The adaptation of four orthorexia nervosa scales into Turkish population
Meeting Abstract